PENGARUH KEPEMIMPINAN PEMERINTAHAN DALAM INOVASI KEBIJAKAN LAYANAN PUBLIK DI KABUPATEN TULANG BAWANG - Winarti; Murtir Jeddawi; Sampara Lukman; Agus Fatoni (GoAcademica Research dan Publishing, 2021)
The quality of public services is the main parameter in the success of an autonomous region in implementing decentralization. Leadership is a very important dimension in the quality of public services. With the innovation of the leader or regional head, it can improve the quality of public services in the area. Thus the purpose of this study is to examine the influence of government leadership in public service policy innovation in Tulang Bawang Lampung Regency which can improve service quality. This research uses a mixed method or often referred to as a mixed method with a sequential explanatory method. The results showed that government leadership had a strong influence on public services. From the research findings, it is revealed that almost all dimensions of government leadership variables have a dominant influence due to the large role of the leader for employees where a leader can influence and influence the behavior of employees or subordinates so that if there is public service innovation from the regional head it can have an influence service quality.